Economic Effect of Rooftop Photovoltaic Penetration on Retail Rates of Bangalore Electricity Supply Company - Gajjar, Jaymin; Raizada, Swasti; Kumar, Vikash; Abraham, Nikhil; Ghosh, Saptak (International Journal of Energy Economics and Policy, 2018)
India has a target of achieving 100 GW of installed solar capacity by 2021-22. Of this, 40 GW will be in the form of rooftop photovoltaic (RTPV) systems. Karnataka has an RTPV target of 2.3 GW, with its largest distribution utility – Bangalore Electricity Supply Company Limited (BESCOM) – expected to contribute 1 GW by 2021-22. This research article focuses on the impact of this capacity addition on BESCOM’s retail rate for downstream consumers considering the present RTPV policy which includes both net-metering and gross-metering mechanisms for specific consumer categories in the state. In order to conduct this exercise, the Annual Revenue Requirement (ARR) of BESCOM has been calculated for the years 2015-16 to 2021-22. The projected energy demand for BESCOM in this timeframe has been estimated based on a compounded annual growth rate of 5.13%. Power purchase costs including annual capacity additions of RTPV have been obtained and these have been observed to rise from Rs. 11,750 Cr. to Rs. 19,100 Cr. in the control period. Subsequently, the average realisation rate has been computed after the ARRs for each year have been determined. The difference between average realisation rates with and without RTPV has been shown to be the impact of RTPV on BESCOM’s retail rates. It has been quantified that with RTPV penetration, the increase in average realisation rate rises by Rs. 0.68/kWh to Rs. 2.32/kWh during the timeframe of seven years. In order to reduce this economic burden across consumer categories, BESCOM needs to improve its distribution network and reduce losses. Apart from this, it has been seen from global energy market dynamics that there has been a decline in PV prices and an increase in the prices of fossil fuel-based electricity. The results that have been presented in this article are likely to be offset marginally owing to these trends. Keywords: Rooftop Photovoltaic, Distribution Companies, Net-metering, Gross-metering, Annual Revenue Requirement, Average Realisation Rate JEL Classifications: G18, C30, Z18, H41 & H50 DOI: https://doi.org/10.32479/ijeep.6036